Bases for the study of the safety of medicines. The spectrum of rare and unexpected ad-verse reactions of bisphosphonates - I S Dydykina; P S Dydykina; Yu V Muravyev (Современная ревматология, 2011)
The paper presents a classification of adverse drug reactions and their characteristics. Bisphophonates (BP) that are have been prescribed for more than 30 years to prevent and treat all forms of osteoporosis (OP) and recognized as first-line drugs for its treatment are used as an example to see the history of investigating rare and unexpected adverse reactions. The direct correlation between the rare adverse reactions of Ps and their use remains to be proven today. The proposal to reduce the prescriptions of BPs is unfounded. The evidence for the efficacy and safety of BPs in OP has been obtained and confirmed by multiple trials and many years X real practice. Alendronate (fosavance) is the most studied BP now.